Recent advances in modeling and simulation of the exposure and response of tungsten to fusion energy conditions. (9th June 2017) - Marian, Jaime; Becquart, Charlotte S.; Domain, Christophe; Dudarev, Sergei L.; Gilbert, Mark R.; Kurtz, Richard J.; Mason, Daniel R.; Nordlund, Kai; Sand, Andrea E.; Snead, Lance L.; Suzudo, Tomoaki; Wirth, Brian D.
Abstract: Under the anticipated operating conditions for demonstration magnetic fusion reactors beyond ITER, structural and plasma-facing materials will be exposed to unprecedented conditions of irradiation, heat flux, and temperature. While such extreme environments remain inaccessible experimentally, computational modeling and simulation can provide qualitative and quantitative insights into materials response and complement the available experimental measurements with carefully validated predictions. For plasma-facing components such as the first wall and the divertor, tungsten (W) has been selected as the leading candidate material due to its superior high-temperature and irradiation properties, as well as for its low retention of implanted tritium. In this paper we provide a review of recent efforts in computational modeling of W both as a plasma-facing material exposed to He deposition as well as a bulk material subjected to fast neutron irradiation. We use a multiscale modeling approach—commonly used as the materials modeling paradigm—to define the outline of the paper and highlight recent advances using several classes of techniques and their interconnection. We highlight several of the most salient findings obtained via computational modeling and point out a number of remaining challenges and future research directions.